SOSIOLEK MASYARAKAT KECAMATAN BURNEH KABUPATEN BANGKALAN (KAJIAN SOSIOLINGUISTIK) - Zeinab, Zeinab (Jurnal Sastra Aksara, 2018)
Sosiolek or social dialect is a variation of language with respect to the status, class and social class of its speakers, such as age, education, sex, occupation, nobility, socioeconomic conditions, and as such. This study aims to describe the use of Indonesian sociolect by age, education, the economy of its speakers in daily communication in the community Burneh district Bangkalan. The method used is the method of observation is by observing the object of study in context. Techniques used are techniques Refer, See, Ably (SLBC) and continue using the technique of note. The subject of this research is the community of Burneh sub-district of Bangkalan Regency. The object of research is the use of Indonesian sociolect in an informal conversation that is spoken directly by the Burneh sub-district community. The use of Indonesian Language sociolect is the use of the Indonesian language based on the level of the speakers and the opponent he said. The occurrence of the variation of Indonesian language due to differences between speakers and opponents and the difference is seen from the choice of words, content, or the content of the conversation.